Direct Versus Indirect Approach in Seasonal Adjustment - Marcus Scheiblecker (Austrian Institute of Economic Research (WIFO), 2014)
With seasonal adjustment one has to decide whether to seasonal adjust an aggregate like GDP directly or to sum up its seasonally adjusted components. This choice is usually driven by subjective motives or practical convenience. In the case of seasonal adjustment with chain-linked data one might feel forced to use the direct approach as components do not even add up to aggregates before the adjustment. This paper presents a guide for practitioners, which recommends a more objective way of decision-making, based on several indicators. It proposes some of these criteria which can facilitate the decision between the direct and the indirect approach. For the case of chain-linked series, where the indirect approach seems not to be feasible because components are not adding up to an aggregate, the paper presents a method how the indirect approach of seasonal adjustment nevertheless can be applied. Finally it deals with a possible balancing process between the results of the direct and the indirect approach and a practical application example is given.
Keywords: 330; Seasonal adjustment; direct indirect method; chain-linking; Bruttoinlandsprodukt; Saisonkomponente; Theorie